Retooling conditional gene expression using a floxed exon. Issue 8 (August 2022) - Kroetz, Mary B.
Abstract : The Cre- lox system is a powerful approach for the spatiotemporal regulation of gene expression. Shaffer and Greenwald recently devised an adaptation of this system in which a floxed artificial exon promotes premature termination of translation and nonsense-mediated decay of mRNA, allowing for robust conditional regulation of transgenes and endogenous loci.